Exclusive Association of p53 Mutation with Super-High Methylation of Tumor Suppressor Genes in the p53 Pathway in a Unique Gastric Cancer Phenotype. - Mina Waraya; Keishi Yamashita; Akira Ema; Natsuya Katada; Shiro Kikuchi; Masahiko Watanabe (PLoS ONE)
Background A comprehensive search for DNA methylated genes identified candidate tumor suppressor genes that have been proven to be involved in the apoptotic process of the p53 pathway. In this study, we investigated p53 mutation in relation to such epigenetic alteration in primary gastric cancer. Methods The methylation profiles of the 3 genes: PGP9.5, NMDAR2B, and CCNA1, which are involved in the p53 tumor suppressor pathway in combination with p53 mutation were examined in 163 primary gastric cancers. The effect of epigenetic reversion in combination with chemotherapeutic drugs on apoptosis was also assessed according to the tumor p53 mutation status. Results p53 gene mutations were found in 44 primary gastric tumors (27%), and super-high methylation of any of the 3 genes was only found in cases with wild type p53. Higher p53 pathway aberration was found in cases with male gender (p = 0.003), intestinal type (p = 0.005), and non-infiltrating type (p = 0.001). The p53 pathway aberration group exhibited less recurrence in lymph nodes, distant organs, and peritoneum than the p53 non-aberration group. In the NUGC4 gastric cancer cell line (p53 wild type), epigenetic treatment augmented apoptosis by chemotherapeutic drugs, partially through p53 transcription activity. On the other hand, in the KATO III cancer cell line (p53 mutant), epigenetic treatment alone induced robust apoptosis, with no trans-activation of p53. Conclusion In gastric cancer, p53 relevant and non-relevant pathways exist, and tumors with either pathway type exhibited unique clinical features. Epigenetic treatments can induce apoptosis partially through p53 activation, however their apoptotic effects may be explained largely by mechanism other than through p53 pathways.